Tension‐free vaginal tape for treatment of pure urodynamic stress urinary incontinence: efficacy and adverse effects at 17‐year follow‐up. (22nd February 2018) - Braga, Andrea; Caccia, Giorgio; Sorice, Paola; Cantaluppi, Simona; Coluccia, Anna Chiara; Di Dedda, Maria Carmela; Regusci, Luca; Ghezzi, Fabio; Uccella, Stefano; Serati, Maurizio
Abstract : Objective: To assess the efficacy and safety of retropubic tension‐free vaginal tape (TVT) 17 years after implantation for the treatment of female pure stress urinary incontinence (SUI). Patients and Methods: A prospective study was conducted in two urogynaecological units in two countries. All consecutive women with urodynamically proven pure SUI treated by TVT were included. Patients with mixed incontinence and/or anatomical evidence of pelvic organ prolapse were excluded. Data regarding subjective outcomes (International Consultation on Incontinence Questionnaire–Short Form, Patient Global Impression of Improvement, and patient satisfaction scores), objective cure (stress test) rates, and adverse events were collected during follow‐up. Univariable analysis was performed to investigate outcomes. Results: A total of 52 women underwent TVT implantation. At 17‐year follow‐up, 46 women (88.4%) were available for the evaluation. We did not find any significant change in surgical outcomes during this time. At 17 years after surgery, 41 of 46 women (89.1%) declared themselves cured ( P = 0.98). Similarly, at 17‐year evaluation, 42 of 46 women (91.4%) were objectively cured. No significant deterioration in objective cure rates was observed over time ( P for trend 0.50). The univariate analysis did not find any risk factor statistically associated with the recurrence of SUI. Of the 46 women, 15 (32.6%) reported the onset of de novo overactive bladder at 17‐year follow‐up. No other late complications were reported. Conclusions: The 17‐year results of this study showed that TVT is a highly effective and safe option for the treatment of SUI.